The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/j.1445-2197.2011.05970.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in body composition after pancreaticoduodenectomy

Abstract: Although at 6 months, important measures of the metabolically functioning tissue, TBP and TBK, have returned to preoperative values significant losses occurred during the first 3 weeks after discharge from hospital and FM did not return to preoperative values. These results suggest the need to improve post-discharge nutritional care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Although few prior studies have characterized changes in either nutritional indices or body composition following pancreatectomy [2932], the results of those studies, together with the data described herein, clearly document that adverse physiologic changes do occur and, more importantly, that they persist long after surgery. In this study, patients experienced a significant loss of weight and serum albumin, and a progressive depletion of both muscle and fat, in the year following PD.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although few prior studies have characterized changes in either nutritional indices or body composition following pancreatectomy [2932], the results of those studies, together with the data described herein, clearly document that adverse physiologic changes do occur and, more importantly, that they persist long after surgery. In this study, patients experienced a significant loss of weight and serum albumin, and a progressive depletion of both muscle and fat, in the year following PD.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, patients experienced a significant loss of weight and serum albumin, and a progressive depletion of both muscle and fat, in the year following PD. In a study of physiologic changes that occurred in 27 patients during the first 6 months following PD, Aslani et al found that both fat mass and total body protein declined in the early postoperative period but by 6 months measures of protein (but not fat mass) returned to preoperative levels [29]. In a more recent study, Hashimoto et al found that 93 patients who underwent pancreatectomy had lost 8.4% of body weight at 2 months after surgery and 9% of body weight by 4 months [33].…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients with PEI are currently limited, although one study in CF (97% of patients with PEI) assessing body composition by dual-energy Xray absorptiometry highlighted a reduction in fat-free mass that did not always correlate with changes in BMI percentile [46]. One group studied changes in body composition using in vivo neutron capture, bioelectrical impedance, skin-fold thickness and circumference after pancreaticoduodenectomy and observed significant drops in all markers in the first 3 months [47]. However, these studies did not sub-group patients by PEI status; therefore the reductions in muscle and fat stores cannot be correlated with PEI.…”
Section: Other Anthropometric Assessmentsmentioning
confidence: 95%
“…Data on the use of other anthropometric measures to assess PERT efficacy are limited. One study noted that PERT use starting 1 month after pancreaticoduodenectomy resulted in a return to pre-operative levels in total body protein, potassium and arm muscle area, but not fat mass, at 6 months [47].…”
Section: Other Anthropometric Assessmentsmentioning
confidence: 98%
See 1 more Smart Citation